A new procedure to determine equivalent strut of infill walls with openings for engineering applications. Issue 4 (4th April 2019) - Tabeshpour, Mohammad Reza; Noorifard, Azadeh
Abstract : In architecture, design of doors and windows for functional requirements, circulation, natural light and ventilation, aesthetics and view is inevitable. Parameters such as size, location and aspect ratio of the openings change the seismic behaviour of infilled frames. Ignoring these parameters in structural analysis may lead to substantial inaccuracy in predicting the lateral stiffness, strength and ductility of the frame. Despite numerous experimental and numerical studies on perforated infill walls in recent decades, the related provisions are rare in seismic codes and engineers tend not to use their results in analysis and design due to their complexity. The main purpose of this work was to propose a new procedure to determine the specifications of equivalent struts of perforated infill walls for engineering applications considering structural stiffness and load path based on valuable existing literature. All common types of windows used in architectural design (central openings, eccentric openings, corner openings and full-length openings) were investigated and the literature was reviewed for reduction factors of equivalent struts of infill walls with openings. Where there was a lack of studies, 27 micro models and 14 macro models were analysed to achieve the purpose of the research. A comprehensive and practical algorithm based on the size and location of openings is proposed.